Contribution of Word length in Substitution Error Pattern analysis of Punjabi Typed Text - Bhagat, Meenu (International Journal of Computer Sciences and Engineering, 2025)
Spelling error pattern analysis of a language is useful in language related technology, such as creation of Natural Language Interfaces, Machine Translation, Optical Character Recognition, Spell Checker and Corrector etc. It includes analysis of various types of errors (insertion, deletion, transposition, substitution, run-on, split word error) Positional analysis, Word length effects, Phonetic errors, First position error analysis, Keyboard effects etc. This paper mainly focuses on the effect of word length in substitution error pattern analysis of Punjabi by doing Statistical Error analysis of Punjabi typed text. It also presents a brief overview of effect of word length on non-word error analysis in Punjabi Typed Text. This paper is based on the analysis done on 20000 misspelled words generated by typists.